FAKTOR-FAKTOR YANG MENYEBABKAN KECELAKAAN KERJA PADA PEKERJA BAGIAN PENGELASAN DI PT. JOHAN SANTOSA - Ridho Amelita Amelita (Universitas Pahlawan, 2019)
Work accident is an unexpected and undesirable event that disrupts the activities of workers at work, causing harm to workers and the company. Some factors that cause work accidents include knowledge, motivation and the use of PPE. The purpose of this study was to determine the factors that cause workplace accidents in the Welding section employees at PT. Johan Santosa. Quantitative research design with Cross Sectional design, this research was carried out on 26-28 July 2018 at PT. Johan Santosa. The population in this study were 45 welding workers. The sampling technique used is total sampling. The instrument used was a questionnaire. The data obtained were analyzed by chi square test, the significance level was 95%. Based on the results of the study showed that there was a significant relationship between knowledge and workplace accidents, this was evidenced by the p value (0,000)